LOBACHEVSKIY GEOMETRIYASI VA UNING ZAMONAVIY MATEMATIKADA QO`LLANISHI - Muxtorova Nozima Farhodjon qizi, Maxmudova Dilnoza Xayitmirzayevna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The article discusses the main concepts of Labachevskiy geometry, created by Nikolay Ivanovich Labachevskiy, and its development. It also highlights the significance of Labachevskiy geometry in mathematical theories and modern scientific fields, analyzing its role in scientific research and practical applications.